Kompatibilitas Sintering dan Fraksi Volume Terhadap Sifat Mekanik Komposit Hybrid: Compatibility of Sintering and volume fraction on Hybrid Composite Mechanical Properties - Agus Pramono; Adhitya Trenggono; Fatah Sulaiman (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2019)
Composite is a combination of two or more of element materials to produce a characteristic that is better than the basic material. The use of two or more elements in the composition of composite materials (Hybrid composite) is expected to combine the properties of each element such as Aluminum which has good elasticity and zinc has good corrosion resistance, graphite has high hardness, and the use of magnesium which is a wettability on good of coupling agent so that the alloy can be used to combine a combination of superior properties in the form of high strength at room temperature, formability and high corrosion resistance. Powder metallurgical technology is very suitable to be applied for the use of more than two elements in the manufacturing of composite materials, because the compressibility of the powder is able to be combined with emphasis and heating, with the use of suitable temperatures. The pressure used is using 200-500 bar on press machine with variations of temperature were 400°C, 450°C and 500°C and variations in volume fraction: 40% Al, 20% Zn, 30% C, 10% Mg: 35% Al, 25% Zn, 30% C, 10% Mg dan 30% Al 30%, Zn, 30% C, 10% Mg. The results of study obtained ideal temperature 400°C, because at this temperature, zinc does not melt, resulting in a bond between the combined elements. At temperatures above 400°C zinc melts and causes a decrease in the mechanical properties of the material. The temperature compatibility of sintering with volume fraction of 35% Al, 25% Zn, 30% C, 10% Mg is able to produce a solid phase in zinc as a matrix with aluminum, the product reaction from composite Al-Zn-C-Mg hybrids which are scattered Al12Mg17 among composite formed phases resulting from powder metallurgy of technology